2022
DOI: 10.3390/antiox11071356
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Mitochondrial Dysfunction, Oxidative Stress, and Progression of Chronic Kidney Disease

Abstract: Acute kidney injury (AKI) and chronic kidney disease (CKD) are interconnected conditions, and CKD is projected to become the fifth leading global cause of death by 2040. New therapeutic approaches are needed. Mitochondrial dysfunction and oxidative stress have emerged as drivers of kidney injury in acute and chronic settings, promoting the AKI-to-CKD transition. In this work, we review the role of mitochondrial dysfunction and oxidative stress in AKI and CKD progression and discuss novel therapeutic approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 170 publications
(236 reference statements)
0
26
0
Order By: Relevance
“…Oxidative stress caused by excessive ROS production and the occurrence as well as progression of CKD have been reported in several prior studies (Fontecha-Barriuso et al, 2022;Rahman et al, 2022). Oxidative stress can induce substantial chronic inflammation often observed in the process of renal injury and fibrosis, ultimately leading to the renal dysfunction.…”
Section: Discussionmentioning
confidence: 80%
“…Oxidative stress caused by excessive ROS production and the occurrence as well as progression of CKD have been reported in several prior studies (Fontecha-Barriuso et al, 2022;Rahman et al, 2022). Oxidative stress can induce substantial chronic inflammation often observed in the process of renal injury and fibrosis, ultimately leading to the renal dysfunction.…”
Section: Discussionmentioning
confidence: 80%
“…Based on the above, we consider our work’s perspective is useful in identification of proteins from the renal mitochondrial protein profiles which could be potential biomarkers of ON or therapeutic targets. In line with the latter, experimental results have shown that OXPHOS [ 53 , 54 , 55 ], inhibition of glycolysis [ 19 , 20 ], or enhancing FA metabolism [ 50 , 56 , 57 , 58 , 59 ] are potential therapeutic strategies related to the mitochondrial function that might decrease renal damage in the UUO.…”
Section: Discussionmentioning
confidence: 81%
“…Oxidative stress takes on a critical significance to the development of AKI. Since myoglobin produced by rhabdomyolysis enters the kidney, considerable ROS is metabolized to produce lipid peroxidation, thus increasing oxidative damage and inducing inflammatory responses [ 61 , 62 ]. MDA and SOD are important indicators of the level of oxidative stress, representing the degree of lipidation of oxygen radicals and the activity of antioxidant enzymes, respectively [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%